Post-Pandemic Trends in Mathematics Education: A Bibliometric Study on the Flipped Classroom Approach (2022-2024) - Griffin Lurim Sebastian Sihite; Della Maulidiya; Yaniasih Yaniasih; Ekawati Marlina; Elwan Stiadi (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Flipped classroom pedagogy has emerged as an innovative approach in mathematics education, promising to enhance student engagement, deepen conceptual understanding, and improve learning outcomes. This study aimed to map the research landscape of flipped classrooms in mathematics education from 2022 to 2024 through a bibliometric analysis of 253 publications retrieved from the ERIC database. The bibliometric analysis, using Biblioshiny, revealed a significant disparity in author productivity, with a small group of researchers contributing a disproportionate share of publications. Furthermore, the study identified key journals and analyzed the co-occurrence of keywords, revealing two major research clusters: core pedagogical themes and the integration of technology and contemporary challenges. The analysis highlighted the influence of high-impact journals, particularly those from the United Kingdom and the United States, on the field. These findings underscore the need to encourage collaboration among researchers, diversify funding sources, and promote equitable access to research publications to ensure a more inclusive and impactful research landscape in flipped classroom mathematics education.